ENHANCING FINANCIAL LITERACY OF PRIMARY SCHOOL TEACHERS THROUGH CURRICULUM-BASED THEMATIC TRAINING - Romantica, Krishna Prafidya; Husni Johan, Arsyelina; Andriani, Rosa; Naili Muna, Siti Umamah; Hasvi, Ismail (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Financial literacy training for elementary school teachers is a strategic initiative to instill basic financial management skills in students through curriculum integration. This community service program was conducted at SDN Pengasinan 1 with 26 participating teachers. The activities included material delivery, group discussions, thematic lesson plan development, and evaluation using digital pre-tests and post-tests via the Kahoot app. Pre-test results indicated a low initial understanding, with an average correct response rate of 44.29%. After the training, post-test results showed significant improvement, reaching 85.71%. Analysis revealed increased understanding in nine of ten financial literacy indicators, though a decline was observed in grasping basic concepts, suggesting the need to reinforce fundamental materials. Overall, the thematic and participatory approach proved effective in enhancing teachers’ competencies in financial literacy and demonstrates potential for replication in other elementary schools.